Scope of Practice, Role Legitimacy, and Role Potential for Cancer Care Coordinators - Stacey Panozzo; Anna Collins; Sue-Anne McLachlan; Rosalind Lau; Brian Le; Mary Duffy; Jennifer A Philip (Elsevier, 2019)
Objective: The cancer care coordinator (CCC) role has become a priority in providing coordinated, patient-centered, supported care for patients, and their families experiencing cancer. The CCC role exists with heterogeneity across tumor streams, clinical disciplines, and institutions. This study explored CCCs perceptions and experiences of their role, scope of practice, and potential for future role development. Methods: This research used a mixed methods design. Focus groups and individual interviews were conducted with a purposive sample of 16 CCCs from two tertiary public teaching hospitals in Melbourne, Australia. A thematic analysis approach was used. A quantitative record of relative time spent on tasks was also collected. Results: Three major themes were identified: (1) Perceptions of role legitimacy, (2) Structure and funding of the role determines scope of practice, and (3) Reflections on the potential for the role. Variability was evident in predominant tasks undertaken, integration into the unit, level of patient contact, and regard from other professional colleagues. Variability appears to relate to employment time assigned to the role, and history and structure of the role. Conclusions: The findings underline the need when establishing and reviewing CCC roles for explicit attention to be given to the reporting, integration, structural, and collegiate support for the role as this will profoundly influence its success.